Developing English Materials for Front Office Course for the Students of Hotel Accommodation of PPLP Dhyana Pura - ., I DEWA MADE BAGUS KASUMAJAYA; ., PROF. DR. NI NYOMAN PADMADEWI, M.A.; ., DR. I GEDE BUDASI, M.Ed.DIP APPLIN (Jurnal Pendidikan Bahasa Inggris Indonesia, 2015)
Penelitian ini bertujuan untuk: (a) mengembangkan materi bahasa inggris kantor depan untuk pengajaran mata kuliah bahasa inggris kantor depan mahasiswa akomodasi perhotelan PPLP Dhyana Pura; (b) mengetahui kualitas materi bahasa inggris kantor depan untuk pengajaran mata kuliah bahasa inggris kantor depan mahasiswa akomodasi perhotelan PPLP Dhyana Pura dari penilaian para ahli. Penelitian ini dirancang dalam bentuk Penelitian dan Pengembangan model Sugiyono (2013). Tahap pertama Penelititan dan Pengembangan model Sugiyono (tahap mengindentifikasi potensi dan masalah atau analisis kebutuhan) menggunakan model analisis kebutuhan Learning Centered Hutchinson dan Waters (1987) untuk digunakan untuk menganalisa kebutuhan target dan belajar mata kuliah bahasa inggris kantor depan. Penelitian ini hanya terbatas dalam pengembangan produk dan uji pakar. Sehingga penelitian ini tidak diarahkan untuk menguji coba produk di lapangan. Materi ajar didesain mengunakan model Hutchinson dan Waters (1987:108) yang terdiri dari input, content focus, language focus, dan task. Hasil penelitian menunjukkan bahwa terdapat 11 unit materi bahasa inggris kantor depan yang sudah dikembangkan. Materi-materi tersebut adalah: (1) Enquiries and Reservations; (2) Giving information about Hotel Facilities; (3) Welcoming Guest and Handling Check-in Guests; (4) Escorting Guests; 5) Explaining Emergency Services and Evacuation Procedures; (6) Events and Tourist Information; (7) Handling Complaint; (8) Handling Check outs and Farewells; (9) Handling Telephone Operator Calls; (10) Successful Interview Skill; (11) Making Covering Letter and Curriculum Vitae. Materi tersebut difokuskan untuk mengembangkan kemampuan berbicara bahasa inggris mahasiswa. Kualitas produk sangat bagus (kualitas produk = 4.14) dan sudah memenuhi kriteria evaluasi materi McDonough dkk (2013). Hasil penelitian ini memberikan kontribusi dalam pengembagan ilmu Linguistik di Bali, Indonesia terutama cabang Linguistik Terapan dalam hal keteresediaan kerangka relevan pengembangan materi ESP yang bisa dipertimbangkan.Kata Kunci : Materi, Mahasiswa, Kantor Depan, Akomodasi Perhotelan This study aimed at: a) developing materials for teaching English for Front Office Course of Students of Hotel Accommodation of PPLP Dhyana Pura; b) knowing the quality of the developed materials for teaching English for Front Office Course of Students of Hotel Accommodation of PPLP Dhyana Pura as perceived by expert judges. This study used R & D model proposed by Sugiyono (2013). Step 1 (identifying the potency & problem phase or need analysis phase) of Sugiyono Model of R&D Design used Hutchinson & Waters’s Learning-Centered Need Analysis Framework (1987) in order to be used to analyze target and learning needs of English for Front Office Course. The present study was limited into developing the product and expert judgment. Therefore, the field test was not conducted in the present study. The materials were designed by following the model of ESP material design of Hutchinson and Waters (1987:108) which consisted of input, content focus, language focus, and task. The findings of this study showed that there were 11 units of English for Front Office material had been developed. Those were; (1) Enquiries and Reservations; (2) Giving information about Hotel Facilities; (3) Welcoming Guest and Handling Check-in Guests; 4) Escorting Guests; 5) Explaining Emergency Services and Evacuation Procedures; 6) Events and Tourist Information; (7) Handling Complaint; (8) Handling Check outs and Farewells; (9) Handling Telephone Operator Calls; (10) Successful Interview Skill; (11) Making Covering Letter and Curriculum Vitae. The materials were focused on developing the students’ speaking ability. The quality of the product was very good (Product Quality = 4.14) and had met the criteria of material evaluation checklist proposed by McDonough et al (2013). These findings had important contribution in the development of Linguistics in Bali, Indonesia, especially Applied Linguistics by providing considerable relevant framework of ESP material construction.keyword : Materials, Students, Front Office, Hotel Accommodation